2023
DOI: 10.3390/cancers15072021
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Inflammatory and Nutritional Biomarkers of Immune Checkpoint Inhibitor Treatment for Recurrent or Metastatic Squamous Cell Carcinoma of the Head and Neck

Abstract: This study aimed to determine the prognostic value of inflammatory and nutritional biomarkers of immune checkpoint inhibitor (ICI) therapy for recurrent or metastatic squamous cell carcinoma of the head and neck (RMHNSCC) and to identify the most useful factor for prognosis assessment. We retrospectively reviewed the medical records of patients with RMHNSCC who received ICI therapy. The response rate for ICI therapy and the relationship between inflammatory and nutritional biomarkers and overall survival were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The salient features of the incorporated articles are succinctly outlined in Table 2 . Three of these investigations were conducted in Japan 23 , 28 , 29 , and five in China 24 , 26 , 27 , 30 , 31 . The range of NOS scores observed in the research encompassed values between 6 and 9, signifying that all included studies exhibited a high level of quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The salient features of the incorporated articles are succinctly outlined in Table 2 . Three of these investigations were conducted in Japan 23 , 28 , 29 , and five in China 24 , 26 , 27 , 30 , 31 . The range of NOS scores observed in the research encompassed values between 6 and 9, signifying that all included studies exhibited a high level of quality.…”
Section: Resultsmentioning
confidence: 99%
“…The range of NOS scores observed in the research encompassed values between 6 and 9, signifying that all included studies exhibited a high level of quality. All seven studies included in the analysis were retrospective 23 , 24 , 26 , 28 31 , while one was single-arm study 27 . Two studies were conducted in patients diagnosed with ESCC patients 30 , 31 ; one study was in HCC patients 27 , one study was in esophageal cancer (EC) patients 26 , one study was in GC patients 24 , one study was in NSCLC patients 23 , one study was in squamous cell carcinoma of the head and neck (HNSCC) patients 28 , and one study was in RCC patients 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we employed a practical machine learning approach to manage high-dimensional data and select relevant hematological biomarkers for prognostic assessment in PPLELC patients undergoing immunotherapy, based on which the HIBS was constructed, comprising 14 factors that reflect aspects of tumor metabolism, systemic inflammation and nutritional status. These factors are known to correlate with tumor development, treatment response and survival outcomes ( 21 - 25 ). We observed that patients in the disease progression group exhibited significantly higher HIBS scores than those in the no-progression group.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous predictors of efficacy have been reported in addition to CPS. While there are factors such as tumor mutational burden (TMB) and T‐cell‐induced gene expression profile 10 that can only be measured with expensive equipment, several biomarkers have been reported as scores that reflect the host's nutritional status and immune response, such as serum albumin level, 11 blood lymphocyte count, neutrophil‐lymphocyte ratio (NLR), 12 and lymphocyte‐to‐monocyte ratio (LMR) 13 . Unlike prospective clinical trials, the present study focused on albumin and neutrophil‐lymphocyte ratio, which are clinically very easy to use, to evaluate their effects on treatment efficacy as well as ultra‐high CPS, considering that patients with different nutritional and immunological conditions will be included.…”
Section: Introductionmentioning
confidence: 99%